The Consumption of Dairy Products Is Associated with Reduced Risks of Obesity and Metabolic Syndrome in Korean Women but not in Men - Lee, Kyung Won (Nutrients, 2017)
We aimed to investigate the association between dairy product consumption and the risk of obesity and metabolic syndrome (MetS) in Korean adults. Data from 13,692 Korean adults aged ≥19 years from the KNHANES 2010–2013 were used. The study participants were divided into three groups according to the serving size of dairy products they consumed based on a single 24-h recall. About 58% of the Korean adults did not consume any dairy products in one day. In both the sexes, only those who adhered to the recommendation for dairy products (≥1 serving/day) achieved the daily requirement of calcium. Women who consumed ≥1 serving/day of dairy products had lower risks of obesity (body mass index ≥ 25 kg/m(2)) (adjusted odds ratio (AOR), 0.77; 95% confidence interval (CI), 0.66–0.89; p for trend < 0.01) and MetS (AOR, 0.67; 95% CI, 0.56–0.80; p for trend < 0.01) than women who did not consume dairy products. However, these significant associations were not observed in men. In conclusion, consuming ≥ 1 serving/day of dairy products could be an easy and efficient strategy for meeting daily calcium requirement as well as lowering risks of obesity and MetS among Korean women.